Movement behaviours in paediatric cancer survivors during recovery and school weeks - Vyhlídal, Tomáš; Dygrýn, Jan; Pelclová, Jana; Chmelík, František (Frontiers in Oncology, 2022)
Purpose Paediatric cancer survivors (PCS) are a high-risk population, who can suffer from late effects of their treatment, such as metabolic syndrome, cardiovascular conditions, secondary tumours. Optimal movement behaviours (e.g., limited sedentary behaviour [SB] and sufficient physical activity [PA]) can reduce the side effects or avoid late effects of their treatment. The aims of this study were to analyse movement behaviours and meeting the recommendation of 60 minutes of moderate-to-vigorous physical activity (MVPA) a day in Czech PCS, and to compare their movement behaviours during recovery and school weeks in relation to gender, age, and cancer type. Methods Twenty-six PCS aged 7-15 years in remission stage took part in the cross-sectional study. Movement behaviours were measured with Actigraph wGT3X+ accelerometers worn 24 hour/day for 20 consecutive days covering recovery week (13 days at recovery camp) and school week (7 days). Based on cancer types, the PCS were categorized into haematological malignancy or solid tumours group. Results In the PCS, movement behaviours differed between recovery and school weeks. During recovery week, the PCS showed less SB (451.8 vs. 552.3 min/day, p < 0.001) and spent more time on light PA (350.3 vs. 255.1 min/day, p < 0.001), moderate PA (73.2 vs. 37.4 min/day, p < 0.001), and vigorous PA (10.3 vs. 4.0 min/day p < 0.001) than during school week. The PA recommendation was met by 77% (n = 20) PCS during recovery week, but only by 15% (n = 4) individuals during school week. Conclusions The PCS recorded higher levels of PA and lower levels of SB during recovery week than during school week. If provided with appropriate conditions, PCS in the remission stage are able to reach the PA level recommended for the healthy population. Recovery week can be a suitable platform for gaining experience that PCS are able to meet the recommended PA level and could be an integral part of reconditioning and resocialization programmes for PCS after the completion of their treatment.